PENGARUH STRATEGI METAKOGNITIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI PERSEPSI SISWA TERHADAP PELAJARAN MATEMATIKA - Suratmi Suratmi; Agustina Sri Purnami (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this research is to know about students problem solving ability between students who implemented metacognitive strategy and conventional strategy, to know about students problem solving ability between student who have high perception, medium perception dan low perception in mathematics, and to know about interaction between of strategy and perception. This research is quasy experimental. The population of this research were students of class VIII SMP Negeri 3 Karangreja year 2014/2015. The sample of this research were 2 class which is 63 students with cluster random sampling technique. Data analysis is used descriptive analysis dan two ways Anava or F-test. The result of this research showed that: The problem solving ability of experiment class better than control class that is ; The problem solving ability of student who have high perception is better than medium and low perception, the problem solving ability of students who have medium perception is equal with low perception that is , and there is no interaction between of strategy and level of perception in problem solving ability that is .